Nitrogen Fertilization on Pearl Millet and Guinea Grass: Phytomass Decomposition, Cellulose, Lignin, and Nutrients Release - Soratto, Rogerio Peres [UNESP]; Martins da Costa, Claudio Hideo; Costa Crusciol, Carlos Alexandre [UNESP]; Neto, Jayme Ferrari; Moro, Edemar (Taylor & Francis Inc, 2019)
Nitrogen (N) anticipation in cover crops, besides increasing the accumulation of dry weight and nutrients, may favor the subsequent crop by increasing the availability of N. However, N can alter the decomposition of phytomass, which could reduce the beneficial effects of cover crops. The objective of this study was to evaluate the decomposition rate and nutrients release from Pennisetum glaucum and Panicum maximum syn. Urochloa maxima as a function of N fertilization. A randomized blocks design with four replicates, constituted by four treatments (pearl millet with N, pearl millet without N, guinea grass with N and guinea grass without and six sampling times (0, 14, 34, 41, 51 and 68 days after management (DAM)). The pearl millet produces more shoot dry weight than guinea grass, and the N fertilization increases the amount of dry weight for both species, but does not alter the decomposition rate. Pearl millet accumulates and releases to the soil large amounts of nutrients followed by guinea grass, regardless of N fertilization. N fertilization increases the amount of N accumulated and accelerates the release of N into the soil. The maximum release rates occur in the period of 0-14 DAM, more intensely with the N fertilization for the N.
Keywords: Pennisetum glaucum; Panicum maximum; nitrogen; straw persistence; nutrients recycling